ACTUALIZING JEAN PIAGET’S THEORY OF COGNITIVE DEVELOPMENT IN LEARNING - Firman Sidik (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This article aimed to investigate the actualization of Jean Piaget’ theory in the learning process, especially those related to the theory of cognitive development. The method in this research was a literature review, in which the data were obtained from various related literature either directly or indirectly. These data were studied with theoretical and philosophical approaches. Then, content analysis was chosen as the technique of data analysis. The data were filtered and classified in order to meet the requirements of scientific work. The results of this study found that Jean Piaget's theory of cognitive development was quite influential in education. In addition, to get the best results in the educational process, all of the components in education should be involved, especially educators who always had to adapt to students’ development. Moreover, appreciation and support for all forms of actualization of the students’ competencies should be provided in order to have a positive impact on the cognitive development of students.